2016
DOI: 10.2147/copd.s115137
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of community-acquired pneumonia in COPD patients with comorbid cardiovascular disease

Abstract: Background and objectiveCOPD patients with community-acquired pneumonia (CAP) have worse clinical outcomes, as compared to those without COPD. Cardiovascular disease (CVD) is a common comorbidity for COPD patients. Whether COPD with comorbid CVD will increase the risk of CAP is not well investigated. The incidence and factors associated with CAP in COPD patients with and without CVD were analyzed.MethodsThe medical records of patients with newly diagnosed COPD between 2007 and 2010 were reviewed. The patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
2
10
0
3
Order By: Relevance
“…In another way, isolated case of this sign as a component of obstructive lung disease may increase the frequency of chest infections and associated morbidity similar to COPD and ILD causing the same. [ 11 ] Moreover, the severity of chest infections/pneumonia may also have been increased by the syndrome due to background respiratory distress similar to the present case. Our case is the first documented pneumonia associated with this syndrome, although cirrhosis itself can increase the risk for the same.…”
Section: Discussionsupporting
confidence: 78%
“…In another way, isolated case of this sign as a component of obstructive lung disease may increase the frequency of chest infections and associated morbidity similar to COPD and ILD causing the same. [ 11 ] Moreover, the severity of chest infections/pneumonia may also have been increased by the syndrome due to background respiratory distress similar to the present case. Our case is the first documented pneumonia associated with this syndrome, although cirrhosis itself can increase the risk for the same.…”
Section: Discussionsupporting
confidence: 78%
“…More recent studies evaluated the risk of pneumonia in COPD patients that also have other co-morbid conditions such as cardiovascular disease (CVD). COPD patients with CVD had increased risk of pneumonia 23 . Lin et al 23 reported that COPD patients with CVD who received inhaled corticosteroids (ICS)-containing therapy had significantly increased risk of developing pneumonia compared to those who did not receive ICS-containing therapy or those who only had comorbid CVD.…”
Section: Epidemiologymentioning
confidence: 99%
“…COPD patients with CVD had increased risk of pneumonia 23 . Lin et al 23 reported that COPD patients with CVD who received inhaled corticosteroids (ICS)-containing therapy had significantly increased risk of developing pneumonia compared to those who did not receive ICS-containing therapy or those who only had comorbid CVD. The increased incidence of pneumonia in COPD patients using ICS is discussed latter.…”
Section: Epidemiologymentioning
confidence: 99%
“…Other risk factors also include comorbid cardiovascular diseases, dementia, prior severe AECOPD events, home oxygen, and inhaled corticosteroids. [ 11 14 ]…”
Section: Introductionmentioning
confidence: 99%